Evaluating the Association Between Methylenetetrahydrofolate Reductase (Rs1801131 and Rs1801133) Gene Polymorphisms and Severity of Coronary Lesions in Patients With STEMI and NSTEMI: A Retrospective Cross‐Sectional Study - Behnam Nazarzadeh; Saeedeh sadat Ghazanfari; Farzaneh Karimi; Seyed ali Moezibady; Fatemeh Salmani; Kazem Dastjerdi; Hamidreza Mohammadi (Health Science Reports)
ABSTRACT Background and Aims Mounting evidence have implicated that rs1801131 and rs1801133, located in the Methylenetetrahydrofolate reductase (MTHFR) gene, may emerge as novel biomarkers for coronary artery disease (CAD). The Synergy between Percutaneous Coronary Intervention with Taxus and Cardiac Surgery (SYNTAX) score is also an appropriate predictor for revascularization strategy in patients with complex CAD. The aim of this study is to investigate the correlation between rs1801131 and rs1801133 with the severity of coronary lesions in patients with ST‑Elevation Myocardial Infarction (STEMI) and Non‑ST‑Elevation Myocardial Infarction (NSTEMI) based on the SYNTAX score. Methods This retrospective cross‐sectional study included 96 patients diagnosed with STEMI and NSTEMI from Razi University Hospital between April and September 2019. Ninety‐six patients were diagnosed with STEMI (N = 43) and NSTEMI (N = 53) were recruited from South Khorasan, Iran. The angiographical characteristics of CAD were defined by the SYNTAX score. Genomic DNA was isolated from peripheral blood and genotyped for rs1801131 and rs1801133 using the TaqMan real‐time PCR method. Results The results of the one‐way analysis of variance indicated that there is no association between rs1801131 and rs1801133 with the severity of coronary lesions in patients with STEMI (p = 0.44) and NSTEMI (p = 0.91). However, the two‐way analysis of variance comparison and post‐hoc test demonstrated that rs1801133 in the presence of rs1801131 is correlated with the SYNTAX score in NSTEMI (p = 0.03) and total patients (p = 0.03). Conclusion In conclusion, our study reveals a significant association between the MTHFR polymorphism rs1801133 and CAD severity, particularly in NSTEMI patients. While rs1801131 showed no correlation, rs1801133 may serve as a valuable genetic biomarker for assessing CAD severity. Further research with larger populations is needed to confirm these findings.